Deixis in English Islamic Friday sermons: A pragma-discourse analysis - Asim Ayed Alkhawaldeh (Universitas Syiah Kuala, 2022)
Although deixis has received increasingly academic attention in linguistic research, its use in sermons, particularly in the Islamic context, has been largely underexplored. Therefore, this paper examined deixis in Islamic Friday sermons from the perspective of pragmatics and discourse analysis. Drawing on Levinson's Framework, it aimed at analyzing three main types of deixis (personal, temporal, and spatial), focusing on their forms, features, functions, and frequency. The data were a corpus of 70 sermons compiled by the researcher from various online websites. The study employed qualitative and quantitative methods to meet the purpose of the study. The findings revealed that these three deictic types were relatively common in the language of the respective corpus with the personal type being predominant, deictically pointing to different referents whose interpretation was sensitive to the context in which they occurred. As an affectively powerful tool in the corpus, the preachers utilized deixis to serve a wide variety of functions on the discourse and pragmatic levels. In the corpus, deictic expressions worked as a discourse strategy to persuade the listeners by drawing their attention and engaging them in the message of the sermon and to signal and organize the flow of information in the ongoing discourse. They also served to enhance togetherness, intimacy, and politeness between the preachers and their audience. This study is hoped to present a good basis for further linguistic investigation of deixis in other languages and religions to illuminate how deictics work in sermonic discourse.